2014
DOI: 10.1002/2014gl059536
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy and subduction-induced mantle fabrics beneath the Arabian and Nubian Plates adjacent to the Red Sea

Abstract: For most continental areas, the mechanisms leading to mantle fabrics responsible for the observed anisotropy remain ambiguous, partially due to the lack of sufficient spatial coverage of reliable seismological observations. Here we report the first joint analysis of shear‐wave splitting measurements obtained at stations on the Arabian and Nubian Plates adjacent to the Red Sea. More than 1100 pairs of high‐quality splitting parameters show dominantly N‐S fast orientations at all 47 stations and larger‐than‐norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…The fast polarization direction of shear‐wave splitting measurements (the α axis of olivine) tends to be parallel to the direction of upper mantle flow or the preferred orientation of melt shape. Shear‐wave splitting measurements show a consistent north‐south orientation of the fast direction [ Wolfe et al ., ; Hansen et al ., ; Elsheikh et al ., ; S. Chen et al ., ]. This seismic anisotropy indicates that northward flow of the asthenosphere may cause the observed seismic anisotropy in the upper mantle beneath the shield, which is in agreement with the north‐south geometry of the LVZ.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The fast polarization direction of shear‐wave splitting measurements (the α axis of olivine) tends to be parallel to the direction of upper mantle flow or the preferred orientation of melt shape. Shear‐wave splitting measurements show a consistent north‐south orientation of the fast direction [ Wolfe et al ., ; Hansen et al ., ; Elsheikh et al ., ; S. Chen et al ., ]. This seismic anisotropy indicates that northward flow of the asthenosphere may cause the observed seismic anisotropy in the upper mantle beneath the shield, which is in agreement with the north‐south geometry of the LVZ.…”
Section: Discussionsupporting
confidence: 88%
“…However, the geometry of the LVZ, with a nearly N‐S direction, does not parallel the Red Sea or the NE relative plate motion. Shear‐wave splitting directions [ Wolfe et al ., ; Hansen et al ., ; Elsheikh et al ., ; B. Chen et al ., ] are parallel to the trend of the LVZ. The geometry of the LVZ and the parallel shear‐wave splitting direction clearly indicate that the passive upwelling of the asthenosphere along the axis of the Red Sea rift is not the primary active process.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Such a long term movement may produce preferred orientation of olivine in the lower lithosphere and the upper asthenosphere, leading to observable anisotropy. This mechanism has been used by Elsheikh et al (2014) to explain dominantly N-S fast orientations observed in Arabia and northern Africa.…”
Section: Formation Mechanisms Of the Observed Anisotropymentioning
confidence: 99%
“…Shear wave splitting measurements obtained adjacent to the Tanzania Craton, the Main Ethiopian Rift, and the Arabian Peninsula [ Bagley and Nyblade , ] are attributed to mantle flow modulated by northward advection of the African superplume which upwells through the mantle transition zone (MTZ) beneath the northern MRZ. However, shear wave splitting studies conducted throughout north central Africa and Saudi Arabia also demonstrate north‐south mantle flow patterns which are attributed to basal traction‐generated anisotropy from simple northward plate migration relative to the underlying asthenosphere [ Elsheikh et al , ; Lemnifi et al , ]. Similarly, shear wave splitting evidence from the Okavango rift zone (ORZ, Figure a) and southern Africa [ Silver et al , ; Yu et al , ] indicates that subcrustal mantle anisotropy can be explained by plate motion and lithospheric Archean structures and are not associated with a contemporary flow system related to the proposed African superplume.…”
Section: Introductionmentioning
confidence: 99%